Pair bond formation leads to a sustained increase in global cerebral glucose metabolism in monogamous male titi monkeys (Callicebus cupreus). (21st April 2017) - Maninger, Nicole; Hinde, Katie; Mendoza, Sally P.; Mason, William A.; Larke, Rebecca H.; Ragen, Benjamin J; Jarcho, Michael R.; Cherry, Simon R.; Rowland, Douglas J.; Ferrer, Emilio; Bales, Karen L.
Highlights: Socially monogamous male titi monkeys were followed longitudinally during pair bond formation. Paired males displayed an increase in global cerebral glucose metabolism until at least four months post pairing. Areas involved in motivation and in social memory displayed higher increases than the whole brain increases. Abstract: Social bonds, especially attachment relationships, are crucial to our health and happiness. However, what we know about the neural substrates of these bonds is almost exclusively limited to rodent models and correlational experiments in humans. Here, we used socially monogamous non-human primates, titi monkeys ( Callicebus cupreus ) to experimentally examine changes in regional and global cerebral glucose metabolism (GCGM) during the formation and maintenance of pair bonds. Baseline positron emission tomography (PET) scans were taken of thirteen unpaired male titi monkeys. Seven males were then experimentally paired with females, scanned and compared, after one week, to six age-matched control males. Five of the six control males were then also paired and scanned after one week. Scans were repeated on all males after four months of pairing. PET scans were coregistered with structural magnetic resonance imaging (MRI), and region of interest (ROI) analysis was carried out. A primary finding was that paired males showed a significant increase in [ 18 F]-fluorodeoxyglucose (FDG) uptake in whole brain following one week of pairing, which is maintained out to four months. Dopaminergic, "motivational" areas and those involved in social behavior showed the greatest change in glucose uptake. In contrast, control areas changed only marginally more than GCGM. These findings confirm the large effects of social bonds on GCGM. They also suggest that more studies should examine how social manipulations affect whole-brain FDG uptake, as opposed to assuming that it does not change across condition.